Europeanisation or De-Europeanisation? Media Freedom in Turkey (1999–2015). Issue 1 (2nd January 2016) - Yılmaz, Gözde
Abstract: The European Union (EU) has successfully been exercising its transformative power through both its enlargement and its neighbourhood policies for decades. Nonetheless, transformation towards a more European model of governance through Europeanisation is not a linear process, but a differentiated one. Adverse consequences for Europeanisation (i.e. de-Europeanisation) have often been neglected. The case of media freedom in Turkey, with a deteriorating trend across time, exemplifies such an outcome. This article explores media freedom in Turkey in the last decade. It argues that media reforms have been reversed over time in a de-Europeanising trend, with the EU losing its position as a reference point for reforms.